Role of Mediation Factors in Social Media Marketing’s Influence on Voting Intentions: Implications for Economic Development and Political Engagement - Sampurno, Ponco; Aruan, Daniel Tumpal Hamonangan (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze social media activity in influencing voting intention through various mediating factors, such as political branding, virality (e-WOM), opinions, trust, and religious beliefs. The study employs a Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS) to examine the relationships between variables in the research model. Data were collected from 226 respondents selected based on specific criteria. The findings indicate that Social Media Marketing significantly influences candidate image, party image, voter trust, voter opinion, virality (e-WOM), religious beliefs, and voting intention. Moreover, party image, voter trust, and voter opinion have significant effects on voting intention, while candidate image, virality (e-WOM), and religious beliefs do not show significant effects. In terms of mediation, voter opinion and party image are proven to mediate the relationship between social media activity and voting intention, whereas other variables do not demonstrate significant mediation effects. This study is expected to provide new insights into how social media interactions affect voting intention. The findings also suggest that the success of political campaigns in the digital era requires strategies tailored to specific audiences based on their demographics, social media usage preferences, and religious beliefs.